AI-driven Alzheimer's disease detection and prediction - Anand, Abhineet 1975-; Kumar, Abhishek 1989-; Lilhore, Umesh Kumar 1982-; Vyas, Narayan 1998-; Yadav, Satya Prakash (IGI Global, 2024)
This book is the culmination of our collaborative efforts, bringing together expertise from various disciplines, including artificial intelligence, computer science, neuroscience, and healthcare. Our shared goal is to address the pressing challenges posed by Alzheimer's disease through innovative AI-driven solutions.
Keywords: Alzheimer's disease -- Diagnosis; Alzheimer's disease -- Diagnosis -- Data processing; Alzheimer's disease -- Treatment; Alzheimer's disease -- Treatment -- Data processing; Artificial intelligence -- Medical applications